Inorganic trace analytics trace element analysis and speciation - Matusiewicz, Henryk; Bulska, Ewa (De Gruyter, 2018)
"Highly accurate chemical speciation and trace element analysis is of great importance in environmental, biological, food sciences, and forensic analysis, as well as in industry. Trace analysis via atomic spectrometry, mass spectroscopy or gas chromatography provides detailed information on chemical forms of elements and elemental trace analysis. This book comprehensively presents sampling and sample preparation, modern analytical techniques, timely application, and quality controlling"--